Pengaruh Enterprise Risk Management Disclosure dan Intellectual Capital Disclosure Terhadap Nilai Perusahaan - Putri, Maysyarah Mahdalena; Setiawan, Mia Angelina (Jurnal Nuansa Karya Akuntansi, 2025)
The research purpose is to reveal and analyze the enterprise risk management (ERM) disclosure and intellectual capital (IC) disclosure impact on the BUMN score listed on the Indonesia Stock Exchange start at 2018 to 2022. The research population comprises all BUMN listed on the IDX for the period in 2018-2022, totaling 14 companies. The data source is secondary data. The technique of sampling used is saturated sampling, where the making population is treated as the sample. The findings shown that ERM disclosure does not have an influence on company score, whereas IC disclosure does have an influence on company score.